The structure of novel C(35) pentacyclic terpenes from Acetobacter xylinum - Förster, Hans J. (1973)
A novel C(35) terpene and its monounsaturated analogue were isolated from cultures of Acetobacter xylinum, together with traces of their C(36) homologues. These substances were found to be hopane derivatives substituted by a five-carbon chain bearing four vicinal hydroxyl groups. For the parent hydrocarbon the term bacteriohopane is proposed. The elucidation of the structures utilized high-resolution mass spectrometry of the terpenes, degradation to C(32) hydrocarbons and detailed mass-spectrometric comparison of these with C(32) hydrocarbons synthesized from known pentacyclic triterpenes. High-resolution mass-spectral data of the terpenes are presented. N.m.r. data are in agreement with the proposed structures, which are further supported by the isolation from the same organism of 22-hydroxyhopane and derivative hopene(s).